2015
DOI: 10.1111/1556-4029.12815
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Challenge in Postmortem Toxicology Applied to a Human Body Found into a Lake after Three Years Immersion

Abstract: The body of a 30-year-old woman was found in Como lake at a depth of about 120 meters in her own car after 3 years of immersion. The aim of this study was to evaluate psychoactive drugs as well as alcohol biomarkers in biological matrices. The following analyses were initially performed: GC-MS systematic toxicological analysis on biological fluids and tissues; GC-MS analysis of drugs of abuse on pubic hair; direct ethanol metabolite determination in pubic hair by LC-MS/MS. After 7 years, the samples, that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Vitreous fluid, blood (central and peripheral), gastric fluid, urine, skeletal muscle, visceral, adipose tissue, sequestered hematomas, and even body hair are all candidates for submission and analysis. The choice of matrices will be limited or suboptimal in cases with prolonged submersion and decomposition, but even with these limitations, qualitative or quantitative results are possible (83). Toxicological analysis of adipocere has yielded useful results (63).…”
Section: Discussionmentioning
confidence: 99%
“…Vitreous fluid, blood (central and peripheral), gastric fluid, urine, skeletal muscle, visceral, adipose tissue, sequestered hematomas, and even body hair are all candidates for submission and analysis. The choice of matrices will be limited or suboptimal in cases with prolonged submersion and decomposition, but even with these limitations, qualitative or quantitative results are possible (83). Toxicological analysis of adipocere has yielded useful results (63).…”
Section: Discussionmentioning
confidence: 99%
“…The alcohol marker EtG (97 pg/mg) was detected in pubic hair. Even though no exhaustive interpretation could be made, the investigation showed that the victim had mental conditions and that she used alcohol, at least socially (Morini et al, 2015).…”
Section: Pm Changes Of Alcohol and Drugs In Submerged Bodiesmentioning
confidence: 99%
“… 37 Also, hEtG has been applied in child custody cases, 38 as well as in examinations of prenatal alcohol exposure. 39 , 40 , 41 , 42 , 43 Further, hEtG has been used in somatic treatment settings 44 , 45 , 46 and is widely utilised in forensic 47 , 48 and criminal justice 49 , 50 , 51 , 52 settings.…”
Section: Introductionmentioning
confidence: 99%